Insulinoma presenting with cardiac arrest and cardiomyopathy. (23rd October 2013) - Thirumalai, Arthi; Levander, Ximena A; Mookherjee, Somnath; White, Andrew A
Abstract : A 33-year-old woman presented with ventricular fibrillation cardiac arrest and was found to have a blood glucose of 1.83 mmol/L. Cardiac catheterisation revealed a dilated left ventricle with an ejection fraction (EF) of 26% and angiographically normal coronary arteries. Continuous dextrose infusion was required to treat hypoglycaemia, which prompted consideration of insulinoma as a possible cause for her cardiomyopathy. Whipple's triad was demonstrated; a 72 h fast provided biochemical evidence of insulinoma, and imaging localised a tumour in her pancreas. The tumour was resected and pathology confirmed insulinoma; pancreaticoduodenectomy cured her hypoglycaemia. No alternate cause of cardiomyopathy was found and 4 months after surgery her EF improved to 41%. High insulin levels can close cardiac KATP channels associated with dilated cardiomyopathy; the catecholamine surge from hypoglycaemia may also contribute to ventricular remodelling. Hypoglycaemia can cause QT segment prolongation, and may have precipitated fibrillation in this patient's arrhythmia-prone myocardium.